ANALISIS MATRIK DAYA TARIK INDUSTRI (MDTI) UNTUK MENENTUKAN POSISI BISNIS - Afandi, Pandi (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2011)
Abstract Business Emulation which progressively kompetitif require brooding of management in chosening and determining business opportunity creatively, inovatif and variatif so that company can survive even forwards progressively grow to expand. There is two determinant as business variable which must be paid attention that is factor of internal and factor of company business in this time for the reference of to determine the position of future business. One of the analysis able to select; choose of with the approach anlyse the MDTI(Matrik Daya Tarik Industri/ Industrial Matrik Fascination). Implementation analyse this relative modesty, that is by identifying Variable external covering : depresiasi currency, Inflation, purchasing power consumer, governmental regulation, wide of market, growth of price, distribution channel, variation of product, efficiency produce the company location, quality of production, ability of management and goods Image. By using hypothesis data utilize to equip the example implemation analyse the MDTI of pursuant to measurement of existing answer quitions assumption with the wight result is such as those which got in this analysis obtained total of score for the variable of external equal to 3.40 and total internal variable score equal to 3.50, so that stay in the matrik diagonal “selective” this cell show the business position in this time with the conclusion that slow even its business growth, but owning potency an opportunity to expand as according to strength poteny owned. Considering progressively tighten the emulation faced by company, hence of vital importance know the strength and exixting business weakness in this time, so that by using approach analyse the MDTI very assisting of the company in determining direction of future business. Keywords : MDTI, External Variable, Internal Variable